(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2024)
Electronic properties of wurtzite silicon (WZ-Si) are investigated by first-principle calculation. It is found that WZ-Si is an indirect band-gap semiconductor at ambient condition. A uniaxial strain along the c-direction can reduce the direct energy gap at Γ significantly. Calculated pressure needed to compress WZ-Si is not too high, which shows strained WZ-Si would be potential in practical use. The effective mass of electron is found strongly dependent on strain which could be used to tailor the transport properties.